Chronicling the Photovoice Dissemination Process: Images and Stories as a Means to Decrease HIV Stigma Among Emerging Health Professionals - Michelle Teti; Latrice C. Pichon; Katina Bitsicas; Mariam Davtyan; Michael Reese (International Journal of Qualitative Methods)
Disseminating images is a critical part of the photovoice process to move ideas to action. Viewers can help translate participants’ experiences to change. Yet, we know relatively little about the decisions made around photovoice dissemination or how photovoice images affect audiences. Relatedly, the audiences of photovoice remain understudied. To help close this gap, we describe a community-academic team’s process of moving photovoice results to change in the Reframing Life with HIV project, to chronicle the details of dissemination. This photovoice project was designed to give young, same gender loving men of color living with HIV (HIV + SGLMOC) in the urban Midwest a space to reframe the discussion around HIV medication adherence. Midway through the project, participants pivoted from planning to share their photo-stories with other HIV + SGLMOC via a photo exhibit – to creating a short video to decrease HIV stigma among emerging health professionals. We describe each step of the process and how the team made decisions about moving the project’s results to action and change. Steps included :1. Photovoice, 2. Post project interviews, 3. Video making, 4. Dissemination of stories via the video to teach others, 5. Project evaluation, and 6. Reflecting on lessons learned and next steps. The video that the participants made helped students understand HIV + SGLMOC, that they are human beings first, not illnesses or solely victims. Unfortunately, however, in post-video surveys, participants reported believing that people of certain races/ethnicities spread HIV, an unintended result of the project. Our findings suggest one way to approach photovoice dissemination, based in resilience and empowerment approaches, that is flexible, prioritizes participants’ project decisions, includes photovoice as one component of ongoing change, and underlines the importance of exploring and responding to viewer response to dissemination.